2017
DOI: 10.3390/ijms18030570
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Glyoxalase I Inhibits Colorectal Tumorigenesis and Tumor Growth via Upregulation of STAT1, p53, and Bax and Downregulation of c-Myc and Bcl-2

Abstract: GlyoxalaseI (GLOI) is an enzyme that catalyzes methylglyoxal metabolism. Overexpression of GLOI has been documented in numerous tumor tissues, including colorectal cancer (CRC). The antitumor effects of GLOI depletion have been demonstrated in some types of cancer, but its role in CRC and the mechanisms underlying this activity remain largely unknown. Our purpose was to investigate the antitumor effects of depleted GLOI on CRC in vitro and in vivo. RNA interference was used to deplete GLOI activity in four CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Most notably, MYC and B7-H3 were downregulated. Interestingly, miR-29 induced a 500-fold upregulation in STAT1 mRNA expression, a molecule implicated in downregulating MYC expression [36,37]. miR-29 downregulated many pro-angiogenic mRNA’s such as VEGFR2, AKT2, MMP2, MMP9, Zap70, MAP2K5 and HIF-1ɑ, further supporting its anti-angiogenesis role in MB (Figure 5A).…”
Section: Resultsmentioning
confidence: 95%
“…Most notably, MYC and B7-H3 were downregulated. Interestingly, miR-29 induced a 500-fold upregulation in STAT1 mRNA expression, a molecule implicated in downregulating MYC expression [36,37]. miR-29 downregulated many pro-angiogenic mRNA’s such as VEGFR2, AKT2, MMP2, MMP9, Zap70, MAP2K5 and HIF-1ɑ, further supporting its anti-angiogenesis role in MB (Figure 5A).…”
Section: Resultsmentioning
confidence: 95%
“…STAT1 is generally considered as a tumor suppressor, although there are some reports on its tumor promoting functions 23. A correlation of STAT1 expression in tumor cells with good prognosis has been reported in several types of cancers 25, 26. Accumulating evidence indicated that STAT1 acts as a tumor suppressor at multiple levels: tumor-intrinsic growth control and tumor immune environment modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma cells, down-regulation of STAT1 expression can slow cell growth ( Ah-Koon et al, 2016 ). Additional research has linked STAT1 with the development of many malignant tumors, including breast cancer, myeloma, and renal cancer ( Suyama et al, 2016 ; Chen et al, 2017 ; Qu et al, 2017 ; Josahkian et al, 2018 ). Specifically, STAT1 was shown to regulate p53 activity by inducing phosphorylation of p53 ( Chen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has linked STAT1 with the development of many malignant tumors, including breast cancer, myeloma, and renal cancer ( Suyama et al, 2016 ; Chen et al, 2017 ; Qu et al, 2017 ; Josahkian et al, 2018 ). Specifically, STAT1 was shown to regulate p53 activity by inducing phosphorylation of p53 ( Chen et al, 2017 ). Through such interaction with p53, STAT1 promotes apoptosis, and STAT1 also interacts with the p53 inhibitor MDM2 ( Chen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation